Memories surrounding Tupac Amaru II: an interview with Miguel Angel Farfan - Cabrera Santibañez, Alana (2025)
Based on the theme of the dossier “Body, Art, and Memory,” Miguel Ángel Farfán was interviewed to reflect on the construction of memories through performance.During this conversation, Miguel Ángel shares his reflections on the staging of Túpac Amaru II and its importance in the Cusco region, as a way of reflecting on the imaginaries surrounding Túpac Amaru II, Micaela Bastidas, and other figures who gained importance alongside them. Likewise, we sought to understand how the past not only influences the present in which we find ourselves, but also impacts the future we are building. It explores the ways in which collective and individual memories come to life through embodiment, and how discourses about the past are reproduced, maintained, and reconstructed. This conversation arises from the final research project that Miguel Ángel Farfán carried out to obtain his Master’s degree in Visual Anthropology.